In Vitro Evaluation of Biofilm Dispersal as a Therapeutic Strategy To Restore Antimicrobial Efficacy - Roizman, Dan (2018)
As a proof-of-concept study, the direct impact of biofilm dispersal on the in vitro efficacy of imipenem and tobramycin was evaluated against 3-day-old biofilms of Pseudomonas aeruginosa. Arabinose induction of biofilm dispersal via activation of the phosphodiesterase YhjH in the P. aeruginosa engineered strain PAO1/pBAD-yhjH resulted in increased antimicrobial efficacy and synergy of the imipenem-tobramycin combination. These results support the use of biofilm dispersal to enhance antimicrobial efficacy in the treatment of biofilm-associated infections, representing a promising therapeutic strategy.